Construction of political education in learning Pancasila and citizenship in increasing students' political awareness - Kuwoto, M Ari; Sudarmanti, Rini; Utami, Atika Budhi (Jurnal Civics: Media Kajian Kewarganegaraan, 2024)
This study aims to describe the construction of political literacy in the learning of Pancasila and civics through the development of students' political consciousness in Pasundan 2 Senior High School Cimahi City. This study is a descriptive study with a qualitative approach. The method of identifying the research topic uses a focus, and the data collection method uses interviews, documents, and observation. The data validity check method uses source triangulation. Then, the data analysis method using Miles and Huberman's model includes data reduction, data presentation, and conclusion. The research methodology is qualitative, using a case study methodology. Based on several research findings, citizenship education as a means of legal and political education aimed at students' legal acquisition is still not functioning optimally. The findings indicate that civic education is being implemented within the school curriculum through various activities and assignments such as tours, interviews with local leaders, election coverage activities, OSIS election activities, and school activities. The results indicate that the implementation of civic education through Pancasila learning and civic education involves the development of learning materials and the use of learning models. Civic education for beginners in learning and curriculum. Factors that support or hinder the implementation of civic education include the implementation of the national curriculum, subject teachers, extracurricular activities, availability of facilities and infrastructure, etc.